Pengaruh Insentif dan Lingkungan Kerja Terhadap Prestasi Kerja Pegawai Pada Kantor Badan Perencanaan Pembangunan Daerah (Bappeda) Kabupaten Lahat - Shinta Oktarina (Sekolah Tinggi Ilmu Ekonomi (STIE) Serelo Lahat, 2020)
This study aims to examine the effect of Incentives and work environment to performance of employees at the Office of the Regional Development Planning Board Lahat Regency. Sampling technique used is the census by distributing questionnaires to all 60 employees of the Office of Regional Development Planning Board Lahat. The data analysis in this research using descriptive analysis, normality test, multiple regression analysis, F test ( ANOVA ), and t-test in order to prove the hypothesis of the study. Multiple regression equation obtained is Y = 2,149 + 0,862X1 + 0,109X2 + e or Job Performance = 2,149 + Incentives 0109 + 0862 Work Environment + error. The results of t-test to each independent variable show the sig. value of constants = 0.116 , incentives = 0.011 and working environment = 0.000. This means that Incentives has a positive and significant effect to employee job performance of Regional Development Planning Board Lahat. Working environment also has positive and significant effect to Job Performance of employees of Regional Development Planning Board Lahat. Based on the significance of Anova test or F -test, obtained the F-count 447 870 with a significance level of 0.000. This means that incentives and working environment together (simultaneously) effect to Job Performance the Office of the Regional Development Planning Board (Bappeda) Lahat regency .